The Relationship Between SPWB And Quality Of Life Stroke Patients In Saint Elisabeth Hospital Medan 2022 - Amando Sinaga; Lindawati Simorangkir; Maria Puji Astuti; Gracia Emya Perangin-angin (Jurnal EduHealth, 2023)
Quality of life is an important aspect in a person's life. The quality of life has 4 aspects, namely social relations, physical health, environment and psychology. Stroke patients will experience setbacks from various aspects, as for efforts that can be made by increasing spiritual well-being. In general, spirituality has a correlation with the quality of life, this is because spiritual well-being has a strong relationship with the relationship between others, oneself and God. This study aims to see/analyze a significant relationship between spiritual well-being and the quality of life of stroke patients at outpatient clinic of Saint Elisabeth Hospital Medan 2022. The design in this study is an analytical research design with a cross sectional approach with a total of 31 respondents, Data collection is carried out using a questionnaire and using the Spearman rank rho statistical test. The results of the Spearman rank rho correlation test (p = 0.006) where the p value <0.05, this indicates that there is a significant correlation between spiritual well-being and the quality of life of stroke patients atoutpatient polyclinic of Saint Elisabeth Hospital Medan 2022 where the strength of the relationship is moderate. and in a positive direction with the meaning that the higher the spiritual level of a person, the better the quality of his life. Therefore, the authors hope that spiritual well-being needs to be applied and applied to improve the quality of life in stroke patients